[Znaczek podziemny "Unia NZS"] . Unofficial stamp "NZS Union" - Poczta NZS. (Poczta NZS, 1988)
Black, blue and red print on white paper, with perforation. Stamp with "Poczta NZS" imprint, released on the occasion of the 7th anniversary of the registration of Independent Students' Union (pol. acronym NZS), reproduces the logo of NZS, with listing of Warsaw universities and the repeated word "Union". Price: 30 zł per stamp.